Prediksi Sisa Umur Transformator Berdasarkan Suhu Hotspot pada Gardu Induk Kebonagung - Aris Yusuf Maulana; Arif Afandi; Achmad Farouq Nur Wahyu Ramadhan; Irfan Andriansyah (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
The ever-increasing demand for electrical energy has a direct impact on the workload of transformers as vital components of the power system. Overloading can accelerate transformer insulation degradation through rising hotspot temperatures, thereby shortening its service life. This study aims to predict the remaining life of 150/20 kV transformers at Kebonagung Main Substation based on loading and hotspot temperature data throughout 2025. The methods employed include loading ratio calculation, top oil temperature rise, hotspot temperature, relative thermal aging rate using the Montsinger method, and transformer aging loss. Peak load data and ambient temperature data from Malang City were used as calculation inputs. The results show that transformer 5 experienced underloading in several months (below 40%), while transformer 6 operated within an efficient loading range. The hotspot temperatures of both transformers remained below the SPLN standard limit of 98°C. The aging loss values were 0.00650 for transformer 5 and 0.11484 for transformer 6. Based on these calculations, the predicted remaining life of transformer 5 is 23.993 years, while transformer 6 is 15.923 years. These findings are expected to serve as technical references for maintenance and replacement decision-making to improve power system reliability.